The Jurisdiction of Sharia Supervisory Board in Indonesia Sharia Capital Market - Bagas Heradhyaksa (SALAM: Jurnal Sosial dan Budaya Syar-i, 2020)
AbstractThe capital market is an institution that brings together those who need funds, to develop their business, and those who are excess funds, to make investments. Unlike the concept of financing in banks, the capital market uses the concept of buying and selling shares. So that it can be a solution for a company that wants to develop its business without using debt. Investors can also get profits that are higher than the profits from bank deposits. Thus, the capital market is growing in the middle of society. However, there are some activities in the capital market that are contrary to Islamic principles. Therefore, the Islamic capital market emerged. To oversee activities in the Islamic capital market, the role of the Sharia Supervisory Board is needed. The objective of this article is to find out the jurisdiction governing the Sharia Supervisory Board in the Islamic capital market in Indonesia. The methodology used is qualitative research. The data used in this study is library data. This study found that the existence of the Sharia Supervisory Board already has a legal basis based on the Indonesian Financial Services Authority Regulation. However, there are no specific laws governing the Islamic capital market. So it is necessary to make a special law that accommodates all aspects of sharia in the Islamic capital market, specifically with regard to the Sharia Supervisory Board.Keywords: Capital Market, Sharia Capital Market, Sharia Supervisory Board, Jurisdiction, Indonesia. AbstrakPasar modal adalah lembaga yang mempertemukan mereka yang membutuhkan dana, untuk mengembangkan usahanya, dan mereka yang memiliki kelebihan dana, untuk melakukan investasi. Berbeda dengan konsep pembiayaan di bank, pasar modal menggunakan konsep jual beli saham. Sehingga dapat menjadi solusi bagi perusahaan yang ingin mengembangkan usahanya tanpa menggunakan hutang. Investor juga bisa mendapatkan keuntungan yang lebih tinggi dari keuntungan dari deposito bank. Dengan demikian, pasar modal tumbuh di tengah masyarakat. Namun, ada beberapa aktivitas di pasar modal yang bertentangan dengan prinsip syariah. Oleh karena itu, pasar modal syariah muncul. Untuk mengawal aktivitas di pasar modal syariah, diperlukan peran dari Dewan Pengawas Syariah. Artikel ini bertujuan untuk mengetahui yurisdiksi yang mengatur Dewan Pengawas Syariah di pasar modal syariah di Indonesia. Metodologi yang digunakan adalah penelitian kualitatif. Data yang digunakan dalam penelitian ini adalah data perpustakaan. Studi ini menemukan bahwa keberadaan Dewan Pengawas Syariah sudah memiliki dasar hukum berdasarkan Peraturan Otoritas Jasa Keuangan. Namun, tidak ada undang-undang khusus yang mengatur pasar modal syariah. Sehingga perlu dibuat undang-undang khusus yang mengakomodir semua aspek syariah di pasar modal syariah, khususnya yang berkaitan dengan Dewan Pengawas Syariah.Kata Kunci: Pasar Modal, Pasar Modal Syariah, Dewan Pengawas Syariah, Yurisdiksi, Indonesia